Malaysians’ perception towards 10 promises in 100 days and public acceptance towards the new government (Pakatan Harapan) / Abdul Rauf Ridzuan…[et al.] - Ridzuan, Abdul Rauf; Mohd Fadzil, Faezah Shuhada; Bakar, Mohd Hilmi; Mohammad, Norazlinda (Faculty of Communication & Media Studies, 2020)
After the 14th General Election (GE14), Pakatan Harapan (PH) won the election on 9th of May 2018. This political party had made their manifesto and announced it on 8th of March 2018. This research is focusing on their efforts to implement their manifesto which is (10 promises in 100 days). The researcher decided to take ten pledges that Pakatan Harapan must carry through during their first 100 days of governance. However, only six promises that the researcher decided to choose for the research because not all the promises had been fulfilled and only six that are fulfilled and partially fulfilled. By using Reasoned Action Theory that can be related to public acceptance towards the new government (PH). The questionnaires was distributed to all Malaysian from various states and the questionnaires were disseminated via online survey using Google Doc. Questionnaires were distributed to 200 respondents in various states aged from 20 to 60 years and above. The raw data was analysed by using Statistical Package for Social Science (SPSS). Based on the result by using Multiple Linear Regression method, there are 4 factors which are the most significant that are 1MDB (β=0.491) marks the strongest relationship towards dependent variables and then followed by GST (β=0.276), Level up the Minimum Wage (β=0.184) and PTPTN (β=-0.105). However, there are 2 factors which are not significant that are Fuel Subsidies β=0.276) and EPF of Housewives (β=-0.005). In order to promote the trust and public acceptance towards the new government, Pakatan Harapan need to fulfil the entire manifesto that they have promised to execute.